Evaluasi Penerapan Standar Pelayanan Minimal Pada Ruas Jalan Provinsi Di Kota Kendari Sulawesi Tenggara - Thahirah Muhsin; Ria Asih Aryani S; I Putu Artama Wiguna (Journal of Civil Engineering, 2018)
Road Minimum Service Standards (MSS) is a road’s technical measure that must be realized by the road administrator so that the roads are able to operate in accordance with the service standards stipulated. The stipulation of road MSS is regulated through Regulation of Minister of Public Works No. 01/Prt/M/2014 on Minimum Service Standards of Public Works and Spatial Planning that have two indicators basic road service are the level of good and medium provincial road conditions as well as the connection between activity centers and production centers (connectivity) in the province. This research aims to discuss about evaluation the condition and connectivity of the road that is implemented in the provincial road segments in Kendari City. The method that used in this research are indentified about the existing condition and connectivity of the road and distribute questionnaires to the road users to knowing about their perception about the service of Province’s road in Kendari City with using secondary datas from Dinas Sumber Daya Air dan Bina Marga Provinsi Sulawesi Tenggara dan primary datas from observation on provincial roads in Kendari and questionnaires distribution to road users. Evaluation factors consisting of public services factors that have been implemented on the provincial road segments in Kendari with the Discrepancy Evaluation Method that direct comparison between the data obtained from the observation and interviews with the target achievement stipulated in Ministerial Regulationof Public Works No. 1/PRT/M/2014. The result of this research on 10 (ten) provincial roads in Kendari City shows the level of good and medium provincial road conditions as well about 55,60% with the standard is 60%, the level of the connectivity in the province about 89,40% with standard in the regulation is 100% and according to the perception of road users, level of service road conditions about 49,25% and level of connectivity of the provincial roads in Kendari City is about 81,2%.